Aldol sensor-inspired fluorescent probes for measuring protein citrullination. Issue 27 (29th June 2020) - Chen, Huihong; Zhao, Hailong; Xiang, Lingling; Wu, Haiting; Liang, Yunshi; Huang, Xin-An; Zhang, Jing
Abstract : Inspired by aldol sensors, a novel series of fluorescent probes were developed for measuring and capturing protein citrullination. Abstract : Protein citrullination is an important posttranslational modification on an arginine residue. However, high quality fluorescent probes for measuring the citrullination level and capturing citrullinated proteins are quite limited. Inspired by the similarity between acid-promoted citrulline-labeling reaction and aldol reaction, here we present "turn-on" and "turn-off" fluorescent probes for measuring citrulline levels based on the scaffold of aldol sensors. Further application of the modified probe showed great potential to simultaneously monitor and capture citrullinated peptides.